Thermal gravimetric study of slag from coal slurry gasification and combustion experiment of rotary combustor - Long CHEN; Yuan ZHANG; Naiji WANG; Shi YANG (Meitan kexue jishu)
A coal water slurry gasifier cinder was selected as the research subject to investigate its physical properties, including density, particle size and SEM morphology. The influence of temperature, oxygen concentration and heating rate on the combustion characteristics of ash slag was examined through thermogravimetric analysis. The burnout duration of ash at various constant temperatures and oxygen concentrations was analyzed. Subsequently, an incineration test for the ash was conducted using a rotating cone burner. The findings indicate that the density of wet ash slag ranges from 620 to 650 kg/m3; decarburized fine slag has a density of 421 kg/m3 while decarburized coarse slag measures 465 kg/m3. The median particle size for dried fine slag is recorded at 33.9 μm, whereas dry coarse slag measures 581 μm. The carbon residue in fine slag exhibits a loose and porous structure conducive to combustion processes. Its ignition temperature varies between 540 and 590℃ with a burnout temperature ranging from 598 to 722 °C. At an oxygen concentration of 22% and a heating rate of 30 K/min, peak weight loss reaches ‒12.3%. The apparent activation energy for fine slag combustion spans from 140 to 230 kJ/mol and increases with rising oxygen concentrations; specifically, when oxygen levels increase from 10% to 16%, combustion time decreases by approximately 23.3% to 29.6%. Pilot test results demonstrate that the rotary combustor effectively combusts and vaporizes fine slag steadily; furthermore, the combustion efficiency exceeds over 90% with residual carbon content in fine slag remaining below 5%.